Microbial and Physicochemical Assessment of Soil Contaminated with Cassava Waste Water in Makurdi Metropolis - Joel Odo (International Journal of Applied Biology, 2022)
Environmental pollution is a burning topic of the day. Air, water and soil are being polluted alike. Soil being a "universal sink" bears the greatest burden of environmental pollution. It is getting polluted in a number of ways. There is urgency in controlling the soil pollution in order to preserve the soil fertility and increase the productivity. In this research work, the microbial and physiochemical assessment of soil contaminated with cassava waste water were studied using standard-based method and standard analytical methods. A total of 6 soil samples were obtained from Naka road, North bank and Gboko road. Three of the soil samples were contaminated with cassava waste water and the remaining three soil samples were used as control. The isolation and enumeration of microbial population was carried out using standard-based methods. Standard analytical methods were used to assay for physicochemical properties. The highest bacterial count of 3.40x103 , 2.85x103 and 2.70x103 CFU/g for Naka road, Gboko road and North bank respectively while for uncontaminated soil were 4.70x104 , 2.90x104 and 2.70x104 CFU/g for North bank Naka road, and Gboko road respectively. There is significant difference in the total viable count between contaminated and uncontaminated (P<0.05). The fungal counts for the polluted and control soil ranged from fungi count 1.16 x 103 5.70 x 101 to 1.4×103±2.82×103 CFU/g, respectively. The fungal counts were significantly lower than the bacterial counts (p < 0.05). The bacteria isolates were pseudomonas spp, Bacillus spp, Micrococcus spp, Klebsiella spp, Escherichia coli, Staphylococcus spp, and Proteus spp and for the fungi isolates were Aspergillus spp, Geotrichum spp, Mucor spp and Rhizopus spp. The present study shows that the cassava effluent can have an increasing or limiting effect on the microbial diversity of the polluted soil which could also be attributed to the simultaneous impact on the physicochemical parameters of the soil. Therefore the release of Cassava waste water into the environment should be discouraged; processor should be trained on simple treatment technique on effluents that will make it less harmful to the environment. And there need for public awareness on the danger of releasing effluents into the environment.